Patient Age-Associated Mortality Risk Is Differentiated by BRAF V600E Status in Papillary Thyroid Cancer - Shen, Xiaopei; Zhu, Guangwu; Liu, Rengyun; Viola, David; Elisei, Rossella; Puxeddu, Efisio; Fugazzola, Laura; Colombo, Carla; Jarzab, Barbara; Czarniecka, Agnieszka; Lam, Alfred K; Mian, Caterina; et al. (Journal of clinical oncology, 2018)
Purpose For the past 65 years, patient age at diagnosis has been widely used as a major mortality risk factor in the risk stratification of papillary thyroid cancer (PTC), but whether this is generally applicable, particularly in patients with different BRAF genetic backgrounds, is unclear. The current study was designed to test whether patient age at diagnosis is a major mortality risk factor. Patients and Methods We conducted a comparative study of the relationship between patient age at diagnosis and PTC-specific mortality with respect to BRAF status in 2,638 patients (623 men and 2,015 women) with a median age of 46 years (interquartile range, 35 to 58 years) at diagnosis and a median follow-up time of 58 months (interquartile range, 26 to 107 months). Eleven medical centers from six countries participated in this study. Results There was a linear association between patient age and mortality in patients with BRAF V600E mutation, but not in patients with wild-type BRAF, in whom the mortality rate remained low and flat with increasing age. Kaplan-Meier survival curves rapidly declined with increasing age in patients with BRAF V600E mutation but did not decline in patients with wild-type BRAF, even beyond age 75 years. The association between mortality and age in patients with BRAF V600E was independent of clinicopathologic risk factors. Similar results were observed when only patients with the conventional variant of PTC were analyzed. Conclusion The long-observed age-associated mortality risk in PTC is dependent on BRAF status; age is a strong, continuous, and independent mortality risk factor in patients with BRAF V600E mutation but not in patients with wild-type BRAF. These results question the conventional general use of patient age as a high-risk factor in PTC and call for differentiation between patients with BRAF V600E and wild-type BRAF when applying age to risk stratification and management of PTC.
Keywords: dospělí; nádory štítné žlázy; Prognosis; Humans; staging nádorů; Mutation; věk při počátku nemoci; lidé středního věku; Neoplasm Staging; Risk Assessment; protoonkogenní proteiny B-Raf; Middle Aged; Kaplanův-Meierův odhad; prognóza; Risk Factors; mužské pohlaví; Age Factors; Thyroid Neoplasms; Adult; rizikové faktory; Proto-Oncogene Proteins B-raf; Thyroid Cancer, Papillary; ženské pohlaví; věkové faktory; hodnocení rizik; lidé; Age of Onset; mutace; Male; papilární karcinom štítné žlázy; Kaplan-Meier Estimate; Female